Buyers' response to third-party quality certification: Theory and evidence from Ethiopian wheat traders - Abate, Gashaw T.; Bernard, Tanguy; Bulte, Erwin; Miguel, Jérémy Do Nascimento; Sadoulet, Elisabeth (Wiley, 2026)
When quality attributes of a product are not directly observable, third-party certification (TPC) enables buyers to distinguish between quality levels and reward sellers accordingly. We study the adoption of TPC by traders in smallholder-based agricultural value chains in low-income countries, where traders aggregate products from many small-scale producers before selling in bulk to downstream processors. In this context, the introduction of TPC services has oftentimes failed. We develop a theoretical model identifying how different market conditions affect traders' choice to purchase certified output from farmers. Next, using a novel lab-in-the-field experiment with Ethiopian wheat traders, we examine the model's predictions. Traders’ willingness to specialize in certified output increases with the share of certified wheat in the market, and this effect is stronger in larger markets. However, we find that traders do not optimally respond to variation in the quality of uncertified wheat in the market. We also analyze conditions where traders deviate from optimal behavior and discuss implications for research and policy making to promote TPC in smallholder-based value-chains.